China's Middle East investment policy - Kenderdine, Tristan; Lan, Peiyuan (Eurasian Geography & Economics, 2018)
China's greater Middle East geoeconomic strategy is centered on an external trade and industry policy. This trade and industry policy combines geopolicy and geoeconomic policy to export industrial capacity bases in what amounts to a geoindustrial policy and a parallel trade strategy. Practical coordination is under the umbrella of the central International Capacity Cooperation macro-policy. China's provincial governments are then tasked with offshoring China's industrial capacity to Middle East economies through specialized International Capacity Cooperation funds, which are then coordinated by sectoral industry associations: International Capacity Cooperation Industry Enterprise Alliances. The final industrial policy is then deployed by matching China's provinces and prefectures to external geographies. This amounts to a State Outward Direct Investment Strategy. This paper uses primary sourced Chinese policy documents from central and provincial state administrative agencies to build a historical institutional record. We then employ a Polanyian analysis of the embeddedness of State functions in China's external investment activities and industrial transfers, analyzing China's external trade and industry policy in the Middle East in terms of state–market institutional interrelationality.
Political Science; International Studies
Keywords: China; China policy; Middle East; Middle East policy; foreign investments; foreign relations; geoeconomics; geoindustrial policy; geopolicy; institutional economics; investment policy